Pengiriman Data Realtime PLC ke ERP Odoo dengan Dilengkapi Analisa OEE - Fiqrotin Nur Asita; Muhammad Khoirul Hasin; Zindhu Maulana Ahmad Putra; Ryan Yudha Adhitya; Imam Sutrisno (Computer Science Research and Its Development Journal, 2023)
With the integration of IT (Information Technology) and OT (Operational Technology), the data generated by the OT system can be easily processed and analyzed using the IT system, thereby synergistically increasing the efficiency and productivity of the company. In addition, to maximize machine performance, the Overall Equipment Effectiveness (OEE) method can be applied to monitor production results. Therefore, the authors designed an integration system based on a software connector to connect the Programmable Logic Controller (PLC) with Enterprise Resources Planning (ERP) Odoo. This system facilitates three communication protocols, namely Modbus TCP/IP, Ethernet/IP, and Profinet. As proof of the success of the connector software, a bottle-sorting plant controlled by PLC was made. The data from the plant is acquired by the connector software and sent in real-time to ERP Odoo. In ERP Odoo, an analysis is carried out through manufacturing modules that are custom-made by applying the OEE method as a step in monitoring the production process. Through research conducted, this integration system has been successfully designed and implemented in a bottle-sorting plant. The results of a comparison between manual OEE calculations and OEE calculations in ERP Odoo found an error of 0.161%. Thus, the IT and OT integration system created has been successful and has made the production process more efficient and has provided significant benefits to the company